NIMG-02. 18F-FLUCICLOVINE PET/CT TO DISTINGUISH RADIATION NECROSIS FROM TUMOR PROGRESSION IN BRAIN METASTASES TREATED WITH STEREOTACTIC RADIOSURGERY. (9th November 2020) - Tom, Martin; DiFilippo, Frank; Jones, Stephen; Suh, John; Murphy, Erin; Yu, Jennifer; Mohammadi, Alireza; Barnett, Gene; Huang, Steve; Wu, Guiyun; Obuchowski, Nancy; Ahluwalia, Manmeet; et al.
Abstract: PURPOSE/OBJECTIVE(S): To report descriptive updates of an ongoing pilot trial assessing whether 18 F-Fluciclovine PET/CT, a widely available amino-acid radiotracer, is useful to distinguish radiation necrosis (RN) from tumor progression (TP) among patients with brain metastases. MATERIALS/METHODS: The primary objective is to estimate the accuracy of 18 F-Fluciclovine PET/CT in distinguishing RN from TP. We included adults with brain metastases who underwent prior stereotactic radiosurgery and presented with a follow-up MRI brain (with DSC-MR perfusion) which was equivocal for RN versus TP. Within 30 days of equivocal MRI, patients underwent 18 F-Fluciclovine PET/CT on a Siemens Biograph mCT scanner with a 10 mCi bolus dose immediately prior to PET. PET data were collected in list-mode for 25 mins post-injection and were reconstructed as a static image of data 10-25 mins post-injection, and as a dynamic series of four 5-min frames between 5-25 mins post-injection. Quantitative metrics for each lesion were documented. Lesion to normal brain ratios were calculated. The reference standard was clinical follow-up with MRI brain (with DSC-MR perfusion) every 2-4 months until multidisciplinary consensus (or tissue confirmation) for diagnosis of RN versus TP. RESULTS: From 7/2019-6/2020, 12 of 16 planned subjects with 17 lesions underwent 18 F-Fluciclovine PET/CT. Primary histology was non-small cell lung cancer in 5 patients, breast in 4, melanoma in 2, and endometrial in 1. Among all 17 lesions, ranges of quantitative metrics were: SUVmax, 2.18-12.10; SUVmean, 1.16-7.37; SUVpeak, 1.06-4.45; normal brain SUVmean, 0.19-0.44; SUVmax/normal ratio, 7.50-45.40; SUVmean/normal ratio, 4.20-26.30; and SUVpeak/normal ratio, 3.90-26.40. Follow-up was completed for 5 patients (6 lesions). No adverse events have occurred. CONCLUSION: In this population, 18 F-Fluciclovine produces a wide range of lesion quantitative metric values and uniformly low uptake in normal brain, which may allow accurate discrimination. Ongoing additional accrual and follow up is required.